Dynamic enforcement of bycatch via reproductive value can increase theoretical efficiency. (October 2021) - Michael, Pamela E.; Wilcox, Chris; Barbraud, Christophe; Delord, Karine; Sumner, Michael; Weimerskirch, Henri
Abstract: Managing marine systems is challenging, as many marine species are highly mobile. Albatross exemplify this paradigm, overlapping multiple threats at sea, including bycatch. The typical characterization of bycatch, the number of individuals, ignores the long-term, population-wide repercussions of bycatch. Including an estimate of the reproductive value (RV, the loss of future reproductive contributions, given bycatch) is a complementary tool, incorporating the population-wide repercussions of bycatch. While bycatch management via dynamic spatial management allows management boundaries to move, it requires monitoring and enforcement to be effective. We provide a proof of concept to optimize bycatch enforcement activities by dynamically targeting areas of concentrated future productivity characterized by RV. This paper examined a population of black-browed albatross ( Thalassarche melanophris ) as a case study. We calculate RV and apply it to at-sea distributions. This creates spatiotemporally explicit surfaces used to prioritize times and locations for bycatch mitigation enforcement. Dynamic enforcement has greater theoretical efficiency than static enforcement, but this difference decreases with increasing population-wide RV subject to enforcement. Though there are implementation challenges, many can be reduced with existing tools providing various opportunities. Incorporating RV when characterizing the impacts of bycatch on a population and strategically applying dynamic bycatch enforcement based on RV can be a powerful, efficient component of dynamic ocean management. Highlights: Future reproductive contribution: RV, describes population-wide bycatch impacts. RV compliments current descriptions of bycatch impacts as individuals removed. Dynamic enforcement as a critical component of dynamic ocean management. Dynamic enforcement prioritized by RV is theoretically more efficient than static. Dynamic enforcement by RV can be used to enforce dynamic ocean management.